Musical Instrument and New Siamese-ness: A Role, Practicing Method and Cultural Adaptation of Kong Hui - Tassanawongwara, Chayuti; Sukpan, Buttree (Thammasat Journal, 2026)
In the discipline of musicology, organology is the study of musical instruments that is particularly focused on the history and elements of such instruments. Additionally, the status of instruments pertains to their social and cultural functions, which are also regarded. The Kong Hui is the subject of this paper, which emphasises the cultural adaptation required for studying through a musical instrument and its core concept of existence. The study has basically initiated with the history of the newly created traditional musical instrument. The paper is centred on the Kong Hui due to its history and its importance in the contemporary existence of the traditional music. Kong Hui is obviously a cross-border instrument, both historically and socially. The paper demonstrated that Kong Hui undergoes three phases of adaptation: a transpositional practice, a geographic transfer that crosses nations, and a transition from religious practice to entertainment purpose during the colonial period. Secondly, casting a specific genre into another generic mode is achieved by modifying the system into Thai tune and imbuing the instrument with the Thai traditional image. Thirdly, re-vision in itself, is the most critical aspect of the adaptive process. The Kong Hui is formed in a traditional Thai ensemble that is mingled with other traditional instruments. Additionally, the Kong Hui is recognised as a unique instrument in the Piphat Dukdambhan ensemble, moreover, the Kong Hui’s playing method is regarded as the means of fortifying an authentic image in the Thai music sphere (Thai-ness). It also illustrated the ensemble creation which is influenced by the modernisation of Western impacts during the Siamese nation-building process.